Assesment of the Impact of Habitat Conditions and Land use on the Floristic Diversity of Selected Rush Communities - Grzelak, Mieczysław; Gaweł, Eliza; Majchrzak, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study concerned the assessment of the effect of various habitat conditions and land use on the habitat diversity of rush communities classified as Phragmitetea. The investigations were conducted in the years 2015-2019 in an area particularly interesting in terms of its nature value and abundant in localities of diverse plant communities, located in ecological areas of permanent grassland in the river valleys of the Noteć Leniwa and the Noteć Bystra, as well as the interlevee flood plain of the Warta in the area of Rakowo.
Keywords: rush communities; habitat conditions; floristic diversity; fodder value; yield; szuwary; warunki siedliskowe; różnorodność florystyczna; wartość paszowa; plony